Stability And Numerical Results For A Thermoelastic Joint-Leg-Beam System - Cliff, E.M. (2006)
Rigidizable/Inflatable (RI) materials offer the possibility of deployable large space structures5 and so are of interest in applications where large optical or RF apertures are needed. In particular, in recent years there has been renewed interest in inflatable-rigidizable truss structures because of the efficiency they offer in packaging during boost-to-orbit. However, much research is still needed to better understand dynamic response characteristics, including inherent damping, of truss structures fabricated with these advanced material systems. One of the most important characteristics of such space systems is their response to changing thermal loads, as they move in/out of the Earth’s shadow. We study the thermoelastic behaviour of a basic truss component consisting of two RI beams connected through a joint subject to solar heating.5 and so are of interest in applications where large optical or RF apertures are needed. In particular, in recent years there has been renewed interest in inflatable-rigidizable truss structures because of the efficiency they offer in packaging during boost-to-orbit. However, much research is still needed to better understand dynamic response characteristics, including inherent damping, of truss structures fabricated with these advanced material systems. One of the most important characteristics of such space systems is their response to changing thermal loads, as they move in/out of the Earth’s shadow. We study the thermoelastic behaviour of a basic truss component consisting of two RI beams connected through a joint subject to solar heating.